A modern guide to the informal economy - Williams, Colin C. 1961- (Elgar modern guides, 2023)
"This Modern Guide presents a comprehensive synthesis of contemporary thought on the informal economy, which, far from being a peripheral feature of the global economy, the author demonstrates, is a system in which the majority of the global workforce are employed and which has pervasive detrimental effects; formalising it is therefore a priority for most governments. Employing theoretical and empirical methodologies, Colin C. Williams explores the latest research on methods of understanding and measuring the informal economy in its various forms, and discusses the rationale behind its participants. Its rigorous discussion of the need to shift away from solely using tools that punish the practice and towards aligning social norms with the regulations of formal institutions is complemented by a rich analysis of how jobs and enterprises across the world can be encouraged to make the transition towards formalism. Incentives, education and reform are among the strategies advocated in this Modern Guide's compelling and lucid roadmap for the transition to formality. An invaluable resource for policymakers involved in tax, social security and labour policies, belonging to both governments and supra-national institutions, the book will also be valuable for academics and researchers in sociology, economics and business studies, especially those with an interest in taxation, industrial relations, entrepreneurship and labour economics"